Owoero”: A Health Education Tool to Dispel Teething Myths and Misconceptions – A Report (2018)
Research findings in Nigeria have revealed that misconceptions about teething is common in the society, particularly among individuals from the lower social class. This prompted the development of a twenty four minute video in a local Nigerian language (Yoruba) titled “Owoero” (meaning “ease”) . The video conveys a general message on ease of eruption of teeth in children; void of the long list of perceived symptoms. Videos are powerful communication vehicles and important health education tools. They have been used in many countries and previous researches have shown that videotapes are useful aids in health education This present video is to serve as a culturally appropriate community dental health education tool, with special focus on nursing mothers and pregnant women particularly in south western Nigeria because of their essential role in oral health care of children. The video also targets people from the lower socioeconomic class due to their poor knowledge and practice of oral health .This article describes the rationale behind the choice of a culturally appropriate heath educational video and the process and steps that went into the finished work